SEVEN DETERMINANTS OF THE SIZE OF A MANUFACTURING COMPANY'S VALUE LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018 - 2021 PERIOD - Basuki Sri Rahayu; Darmanto Darmanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The influence of the variables Capital Structure, Solvency, Profitability, Managerial Ownership, Intellectual Capital, Growth and Cash Ownership on firm value is the aim of this research. The population of this research are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 periods. The sample selection used a purposive sampling method, with the provisions of a manufacturing company, having complete financial statements, not using foreign currency in financial statements, experiencing successive profits. The classical assumption test gives the results of all variables normally distributed, there is no multicollinearity, autocorrelation and no heteroscedasticity. The high squared R test and the Model test or F test stated that it was good.Multiple regression analysis was used in this study. The results achieved are that the variables Capital Structure, Solvability, Profitability, Managerial Ownership, Intellectual Capital, Growth and Cash Ownership have an effect on Firm Value Keywords: Capital Structure, Solvency, Profitability, Managerial Ownership, Intellectual Capital, Growth and Cash Ownership, Firm Value.